Exploration of novel opaque16 mutation as a source for high lysine and tryptophan in maize endosperm - Sarika, Konsam; Hossain, Firoz; Muthusamy, Vignesh; Baveja, Aanchal; Zunjare, Rajkumar; Goswami, Rajat; Thirunavukkarasu, Nepolean; Saha, Supradip; Gupta, Hari Shanker (The Indian Journal of Genetics and Plant Breeding, 2017)
In the present study, two F2 populations derived by crossingwild type- (CML533 and CML537) and o16-donor line(QCL3024) were raised and genotyped. The recessiveo16o16 possessed nearly two-fold more lysine (0.247%)and tryptophan (0.072%) in mutants, than wild type (0.125%lysine and 0.035% tryptophan) across populations.However, o16o16 showed wide variation for both lysine(0.111-0.376%) and tryptophan (0.027-0.117%) acrosspopulations, suggesting the role of modifier loci. The studydid not show any significant correlation (r=0.14) betweenlysine and tryptophan, however some segregants with highlysine (>0.300%) and -tryptophan (>0.090%) were identified.Some of the segregants with o16o16 possessed comparablelysine and tryptophan with o2o2 genotypes. These o16o16segregants may serve as novel genetic resource in the QPMbreeding programme, and some of them can be used forenhancement of both lysine and tryptophan in place of o2mutant. This is the first ever report of influence of o16 onaccumulation of tryptophan in maize.